2
$\begingroup$

How to take the derivative of $\prod_{i=1}^{n}(1-e^{-\lambda _{i}\cdot x})I(x>0)$ with regard to x?

Here $F(X)=\prod_{i=1}^{n}(1-e^{-\lambda _{i}\cdot x})I(x>0)$ is a CDF, and I want to take the derivative of it and get the pdf of X.

I try to take the log of F(X), so $\frac{d}{d x}logF(x)=\frac{d logF(x)}{d F(x)}\cdot \frac{d F(x)}{d x}$,

@Ankit Kumar help me with:

$$\frac{d(logF(x))}{dx}=\sum_{i=1}^n\frac{d(log(1-e^{-\lambda_ix}))}{dx}$$, then $$\frac{1}{F(x)}\frac{d(F(x))}{dx}=\sum_{i=1}^n\frac{1}{\log(1-e^{-\lambda_ix})}{\lambda_ie^{-\lambda_ix}}$$, but I don't know how to move on with $\frac{d(F(x))}{dx}=\sum_{i=1}^n\frac{1}{\log(1-e^{-\lambda_ix})}{\lambda_ie^{-\lambda_ix}}\cdot \prod_{i=1}^{n}(1-e^{-\lambda _{i}\cdot x})$, how to simplify it? since it is a multiplication of a sum of sequence and a product of sequence.

$\endgroup$
2
$\begingroup$

Here is another approach. Recall the product formula $(f\cdot g)^{\prime}=f^{\prime}\cdot g+f\cdot g^{\prime}$ of the product of two differentiable functions $f,g$. We can generalise this (and for instance prove it with induction) and obtain \begin{align*} \color{blue}{\left(\prod_{j=1}^n f_j(x)\right)^{\prime}} &=\left(f_1(x)\right)^\prime \prod_{j=2}^nf_j(x)+f_1(x)\left(\prod_{j=2}^n f_j(x)\right)^\prime\\ &=\left(f_1(x)\right)^\prime \prod_{j=2}^nf_j(x)+f_1(x)\left(\left(f_2(x)\right)^\prime \prod_{j=3}^nf_j(x)+f_2(x)\left(\prod_{j=3}^n f_j(x)\right)^\prime\right)\\ &=\left(f_1(x)\right)^\prime \prod_{{j=1}\atop{j\ne 1}}^nf_j(x)+\left(f_2(x)\right)^\prime \prod_{{j=1}\atop{j\ne 2}}^nf_j(x)+f_1(x)f_2(x)\left(\prod_{j=3}^n f_j(x)\right)^\prime\\ &\ \ \vdots\\ &=\left(f_1(x)\right)^\prime \prod_{{j=1}\atop{j\ne 1}}^nf_j(x)+\left(f_2(x)\right)^\prime \prod_{{j=1}\atop{j\ne 2}}^nf_j(x) +\cdots+\left(f_n(x)\right)^\prime \prod_{{j=1}\atop{j\ne n}}^nf_j(x)\\ &\,\,\color{blue}{=\sum_{k=1}^n\left(f_k(x)\right)^{\prime} \prod_{{j=1}\atop{j\ne k}}^nf_j(x)}\tag{1} \end{align*}

We obtain according to (1) \begin{align*} \frac{d}{dx}\left(\prod_{j=1}^n\left(1-e^{-\lambda_j x}\right)\right) &=\sum_{k=1}^n\left(\frac{d}{dx}\left(1-e^{-\lambda_k x}\right)\right)\prod_{{j=1}\atop{j\ne k}}^n\left(1-e^{-\lambda_j x}\right)\\ &=\sum_{k=1}^n\lambda_k e^{-\lambda_k x}\prod_{{j=1}\atop{j\ne k}}^n\left(1-e^{-\lambda_j x}\right) \end{align*}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.